2018
DOI: 10.1039/c7me00126f
|View full text |Cite
|
Sign up to set email alerts
|

Enriched optimization of molecular properties under constraints: an electrochromic example

Abstract: We present a deterministic optimization procedure of molecular properties that ensures diverse coverage of the given chemical compound search space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…R diversity mismatch = − r generated diversity − r training diversity (28) Another diversity measure that has been employed is uniqueness, which aims to reduce the number of repeat molecules. The uniqueness reward R uniqueness ∈ (0, 1] is defined as:…”
Section: Diversity and Noveltymentioning
confidence: 99%
See 1 more Smart Citation
“…R diversity mismatch = − r generated diversity − r training diversity (28) Another diversity measure that has been employed is uniqueness, which aims to reduce the number of repeat molecules. The uniqueness reward R uniqueness ∈ (0, 1] is defined as:…”
Section: Diversity and Noveltymentioning
confidence: 99%
“…While much of the work so far has focused on deep generative modeling for drug molecules, 24 there are many other application domains which are benefiting from the application of deep learning to lead generation and screening, such as organic light emitting diodes, 25 organic solar cells, 26 energetic materials, 10,27 electrochromic devices, 28 polymers, 29 polypeptides, [30][31][32] and metal organic frameworks. 33,34 Our review touches on four major issues we have observed in the field.…”
mentioning
confidence: 99%
“…Consequently, a number of methods have been developed to explore chemical subspaces efficiently. ,,, Lack of structure may express itself in property roughness or constraint-induced feasibility islands. Prominent approaches to address these as well as search space discreteness are stochastic methods, ,,, in particular genetic algorithms (GAs). ,, GAs address the problem of property roughness by using populations of candidates of which not all members are solely evolved by performance.…”
Section: Introductionmentioning
confidence: 99%
“…For logical analysis, we propose use of a feedforward deep neural network model (multilayer perceptron). , The backpropagation algorithm does the training of such a machine learning model . Different computer and machine learning methods are able to solve a lot of biological and chemical problems, in particular, establishing the structure of proteins and their interactions, as well as predicting the effect of mutations on their assembly. , …”
mentioning
confidence: 99%
“…25 Different computer and machine learning methods are able to solve a lot of biological and chemical problems, in particular, establishing the structure of proteins and their interactions, as well as predicting the effect of mutations on their assembly. 26,27 Multilayer perceptron supervised learning allows the detection of individual states on an eGaIn/hydrogel interface that depends on hydrogel composition. A database is necessary for model training.…”
mentioning
confidence: 99%